Study of Proline accumulation and gene expression of P5CS in leaves and flower buds of common bean cultivars under drought stress - Narges Qareqani pour; Behrouz shiran; Mahmoud Khoddam Bashi; Alireza Molaei (مجله بیوتکنولوژی کشاورزی, 2015)
Eleven common genotypes belonging to two different groups (cranberry bean and lima bean) were submitted to drought stress during vegetative and reproductive stage under controlled glasshouse condition. Drought stress was induced at vegetative stage with the appearance of the third trifoliate and at reproductive stage when flower buds were passing through meiosis. Then proline level and D-1-proline -5-carboxylate synthetase (P5CS) gene expression were analyzed. In all genotypes free proline accumulated under drought stress, however proline levels increased earlier in drought-tolerant genotypes compared to more susceptible ones and so the content of free proline in bean flower buds was 10-fold higher than leaves under both conditions of drought and control. The expression of key gene in proline metabolism (P5CS), was studied in the leaves and flower buds of experimental plants by semi-quantitative RT-PCR under drought stress. This abiotic stress caused significant up-regulation of the expression of P5CS. An increase of expression of P5CS was observed in drought-resistant genotypes of bean, compared with sensitive ones. This may be resulted from an increase of the level of final product of the gene. Expression of P5CS gene correlates with the proline levels found in leaf and flower buds tissue.